Accessibility of Persons with Disabilities in Realizing Elections with Integrity - Yusdar Yusdar (Faculty of Law, Musamus University, 2019)
The right to vote and be elected is a constitutional right of citizens who are recognized as part of the rights to the same position in law and government. Elections are a very important momentum, in fact, the Election still often raises problems for persons with disabilities. Persons with disabilities are a group of persons with disabilities who most need special facilities so that they can choose independently so they can fulfill the principle of elections, namely Direct, General, Free and Confidential and Honest and Fair. So that the political rights of persons with disabilities have not been maximally fulfilled through the provision of accessibility in elections for them. This research is normative legal research. By using several methods of approach, namely: Legislative approach (statute approach), conceptual approach (conceptual approach), case approach (case approach). The results of the study show that the provision of accessibility space, not only on the momentum of giving rights (giving ballots to be tested) to persons with disabilities on voting days and hours in elections but giving accessibility to persons with disabilities in elections was given since the stages of election implementation were echoed. Ideally, Disabled Persons must have access as election organizers as well as election participants. The accessibility of persons with disabilities should not only be given to access rights as voters on the day and time of voting.